Tahfidz Al-Qur’an Learning Model in Increasing Students’ Interest And Independence in Learning (Study at Muhammadiyah 22 Junior High School Setiabudi Pamulang South Tangerang City) - Muhamad Nuryasin; Adi Fahrudin; Oneng Nurul Bariyah (Yayasan Adra Karima Hubbi, 2024)
Background: This dissertation is motivated by the increasing number of educational institutions incorporating the Tahfidz Al-Qur’an curriculum into their school programs. Parental awareness of the importance of Tahfidz Al-Qur’an education as a vital provision for their children’s lives is growing. SMP Muhammadiyah 22 Setiabudi Pamulang, South Tangerang City, has garnered particular attention from parents. The modern societal trend towards instant gratification, practicality, and speed may influence students’ self-reliance in learning. Such tendencies can lead to rule-breaking, neglect of moral values, careless work habits, and dependence on others. Objective: The study aims to explain the methods, materials, media, and models of Tahfidz Al-Qur’an learning to foster interest and independence in student learning. This research seeks to develop a comprehensive approach by combining various Tahfidz methods to strengthen and complement each other, thereby achieving optimal memorization results. Methods: The research employs a qualitative methodology. Participants include the school principal and vice-principal, Tahfidz class guardians, Tahfidz mentors, students, and religious figures. Through detailed analysis, the study endeavors to outline a new model for Tahfidz Al-Qur’an learning that addresses the needs and expectations of modern educational environments. Results: The study identifies effective strategies and practices for teaching Tahfidz Al-Qur’an, emphasizing the importance of integrating diverse methods to enhance student engagement and independence. The findings highlight the critical role of a supportive learning environment and the integration of traditional and modern teaching techniques. Conclusion: The research concludes that a new model for Tahfidz Al-Qur’an learning is essential and highly anticipated. This model should incorporate varied teaching methods, materials, and media to foster greater interest and self-reliance among students in their memorization of the Qur’an.